How Were Modified the Human Anatomy Study Habits During and After Confinement by the Covid-19 Pandemic? [¿Cómo Se Modificaron Los Hábitos de Estudio en Anatomía Humana Durante y Después del Confinamiento por la Pandemia del Covid-19?] - Bravo-Barrera, L; Alarcon-Alvarez, E; Iturra-Gonzalez, J; Sanchez-Ramirez, C; Valdes-Orrego, I; Ortiz-Lorca, A (Universidad de la Frontera, 2022)
During 2020 and 2021 the anatomy subject was developed by online classes. In 2022, face-to-face teaching activities were resumed. The objective was to compare the autonomous study habits of two student generations that coursed the Human Anatomy subject in online and face-to-face mode. Two groups of students were asked to fill-out an online questionnaire. Online Generation (OL) (n=185) and Face-to-face Generation (FF) (n=154). The difference between both groups was the learning activities. OL received only online classes, and FF received theoretical classes and laboratory activities in face-to-face sessions. The most of OL subjects had greater clarity about the contents (71.9 %) and the depth (50.8 %) that they should study them, in contrast with FF (58.4 %, p = 0.0124 and 24.7 %, p < 0.0001 respectively). In OL, 47 % spent more than 4 hours weekly studying human anatomy, whereas in FF 68.2 % (p<0.0001). In both groups, the most important resource was the Video Recorded Classes (90.8 % in OL, and 83.1 % in FF). For OL, the three priority resources were exclusively electronic: 1) Video Recorded Classes, 2) Apps on smartphone or tablets, and 3) Apps on laptop or computer. FF generation prioritized: 1) Video Recorded Classes, 2) Anatomy Atlas, and 3) Class Slides. During the COVID-19 pandemic, the students that received only online classes were able to plain their study time in a better way than whose were in face-to-face classes. However, they spent less time to study the topics. In addition, it was possible to determine that students prefer digital resources (video classes recorded and apps in smartphone or computer) over traditional resources such as textbook and anatomy atlas. It proposes to consider these results in the Human Anatomy subjects design, in virtual or face-to-face mode. © 2022, Universidad de la Frontera. All rights reserved.